Antagonistic effects of Bacillus species against bacterial multi-drug resistant (MDR) food-borne pathogens and aflatoxigenic fungi - Temilade Ozabor; Deborah Falomo; Elizabeth Taiwo; Oyindamola Alabi; Precious Adediran; Femi Ayoade; Ilesanmi Fadahunsi; Janet Olaitan (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt